2022
DOI: 10.1186/s12872-022-02556-2
|View full text |Cite
|
Sign up to set email alerts
|

MELD-XI score predict no-reflow phenomenon and short-term mortality in patient with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: Introduction No-reflow phenomenon (NRP) is one of the complications that mostly occur during percutaneous coronary intervention (PCI). In this study, we comprehensively examined the relationship between the model for end-stage liver disease-XI (MELD-XI) score and NRP. Moreover, we discussed whether the MELD-XI score could be considered as an accurate risk assessment score of patients with ST-segment elevation myocardial infarction (STEMI) who are candidates for PCI. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Our study showed somewhat higher percentage of no reflow in primary PCI (31.4%). The finding of higher occurrence of no reflow in people aged > 60 years, females ,15 more time to reperfusion, poor baseline TIMI flow 16 and LAD infarction are the same as in previous studies 5,13,14 However we used a new parameter during our study which was stent diameter. It was found that stent diameter > 3 mm was associated with higher likelihood of no reflow.…”
Section: Discussionsupporting
confidence: 55%
“…Our study showed somewhat higher percentage of no reflow in primary PCI (31.4%). The finding of higher occurrence of no reflow in people aged > 60 years, females ,15 more time to reperfusion, poor baseline TIMI flow 16 and LAD infarction are the same as in previous studies 5,13,14 However we used a new parameter during our study which was stent diameter. It was found that stent diameter > 3 mm was associated with higher likelihood of no reflow.…”
Section: Discussionsupporting
confidence: 55%
“…Admission vitamin D levels have been associated with NRP and may predict NRP after PCI in patients with STEMI [20]. The model for end-stage liver disease-XI (MELD-XI) score can be used to predict NRP and short-term prognosis in patients with STEMI [21].…”
Section: Discussionmentioning
confidence: 99%